2017
DOI: 10.1111/ijun.12143
|View full text |Cite
|
Sign up to set email alerts
|

Identifying reasons, gaps and prevalence of diaper usage in an acute hospital

Abstract: Are diaper usage overused in acute hospital settings? Are there ways to avoid unnecessary diaper usage? This study aimed to identify the prevalence of diaper usage and the reasons of using diaper as well as to suggest strategies to avoid unnecessary use of diaper. Diaper is widely used for patients in hospitals worldwide but is seldom to be report its prevalence. Some patients with medical issues need to use diaper but some who do not have those problems are still given a diaper to wear once admitted. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It is noted that several current studies investigating fecal shedding timelines and intensity for SARS-CoV-2 may in fact be investigating the sickest of patients in a hospital setting ( Chen et al, 2020 ; Fontana et al, 2020 ), and so patterns may not reflect occurrences in the general population, where a significant quantity of patients will likely suffer from milder symptoms, or no symptoms at all ( Pan et al, 2020 ; Park et al, 2020 ). Furthermore, sicker or elderly patients may in fact “fall off” the wastewater monitoring efforts if bed pans or adult diapers are utilized as part of their treatment and convalescence in a hospital or retirement home ( Coelho et al, 2015 ; Tsang et al, 2017 ).…”
Section: Results Discussion and Implicationsmentioning
confidence: 99%
“…It is noted that several current studies investigating fecal shedding timelines and intensity for SARS-CoV-2 may in fact be investigating the sickest of patients in a hospital setting ( Chen et al, 2020 ; Fontana et al, 2020 ), and so patterns may not reflect occurrences in the general population, where a significant quantity of patients will likely suffer from milder symptoms, or no symptoms at all ( Pan et al, 2020 ; Park et al, 2020 ). Furthermore, sicker or elderly patients may in fact “fall off” the wastewater monitoring efforts if bed pans or adult diapers are utilized as part of their treatment and convalescence in a hospital or retirement home ( Coelho et al, 2015 ; Tsang et al, 2017 ).…”
Section: Results Discussion and Implicationsmentioning
confidence: 99%
“…It is not protocol to document this, and the reasons would not be found in the journals. However, other studies have shown that impaired cognitive capacity, low physical functional status, and incontinence at admission are reasons for becoming a user of incontinence pads during hospitalization ( Tsang et al., 2017 ; Zisberg, 2011 ; Zisberg et al., 2011 ). However, in several studies, unnecessary use of incontinence pads during hospitalization has also been found.…”
Section: Discussionmentioning
confidence: 99%
“…Likely, several of the older patients in our study did not have a reason either. In other studies it has been pointed out that national guidelines might reduce the unnecessary use of absorbent incontinence pads and, thereby, urinary tract infections ( Bitencourt et al., 2018 ; Tsang et al., 2017 ). However, despite national guidelines regarding the use of absorbent incontinence pads in Denmark, we have found results comparable to those mentioned above ( Houlind and Klarskov, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation